OPTIMALISASI MANAJEMEN STRATEGI PROGRAM BIAH ARABIYAH DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Anyes Latifatul Insaniyah; Diana Novitasari; Ulva Nurjanah (Institut Agama Islam Darussalam Blokagung, 2021)
Abstract This purpose of this research is to determine the factors of strength and weakness, opportunity and threat factors, as well as optimizing the strategic management of the arabiyah biah program at Pondok Pesantren Darussalam Blokagung Banyuwangi. In this study using qualitative research methods. Data collection techniques with observation, interviews and documentation. The data analysis technique used SWOT analysis and the validity of the data using triangulation. The results of this study indicate that the strength factors are a systematic teaching system, an organized program of activities, good human resources, adequate facilities, and upgrading of tutors conducted every period. While the weakness factors are the inefficient dormitory conditions, the lack of new recruits, the lack of Arabic reference books, the limited time for the activity program, and the absence of a language laboratory. The opportunity factors are the location of the dormitory which is separate from the central boarding school, the formation of language groups in each room, collaboration with Arabic language tutors at the male boarding school, the exchange of students with the Darul Lughah Wadda'wah Islamic Boarding School Bangil Pasuruan, thinking about the quality of the achievements achieved. While the threat factors include the weakening of the Arabic language of female students when they return to the central boarding school, the output cannot create new cadres, female students are only given 15 months to attend courses, and the COVID-19 pandemic. And optimizing the strategic management of the biah arabiyah program including planning administrative activities, internal management meetings, determining tutors, group division and scheduling, implementation that begins with debriefing educators (tutors), program implementation, determining materials and determining learning methods, as well as supervision which includes monitoring and evaluation of learning outcomes.